Le hate dans les commentaires des internautes de la presse sportive - Napieralski, Andrzej (Studia Romanica Posnaniensia, 2017)
In recent years, the Internet has become a place where a new type of users, the “outraged”, have the opportunity to express themselves anonymously on any subject. They take advantage of it to propagate hate just for pleasure. This kind of verbal abuse, which we will consider as a new act of speech, already occupies an important place in the community of web users. This research will examine the hate speech of French football fans, in order to analyze their ways of expressing themselves. It seems that verbal hate is characteristic of younger people, the generation not shocked by the deviant “trolling” behaviors. Hate is expressed in most cases with insults, but it seems to us that it is not the lexemes and their semantic content that play the preponderant role, but above all the context and co-text of the utterances produced by Internet users. Arriving at the definition of the hate phenomenon will be one of the main objectives of this study. We will try to prove that this concept is not identical to those already well-defined, like insults, curses, valves, etc. The hate phenomenon will be illustrated with several examples taken from a corpus of French and Polish comments.